Biomarkers in the Atacama Desert along the moisture gradient and the depth in the hyperarid zone: Phosphatase activity as trace of microbial activity. Issue 5 (26th October 2022) - Kobayashi, Kensei; Nauny, Philippe; Takano, Yoshinori; Honma, Chiho; Kurizuka, Taihei; Ishikawa, Yuto; Yogosawa, Shusuke; Obayashi, Yumiko; Kaneko, Takeo; Kebukawa, Yoko; Mita, Hajime; Ogawa, Mari; et al.
Abstract: Microbiological activities can be detected in various extreme environments on Earth, which suggest that extraterrestrial environments, such as on Mars, could host life. There have been proposed a number of biomarkers to detect extant life mostly based on specific molecules. Because terrestrial organisms have catalytic proteins (enzymes), enzymatic activity may also be a good indicator to evaluate biological activities in extreme environments. Phosphatases are essential for all terrestrial organisms because phosphate esters are ubiquitously used in genetic molecules (DNA/RNA) and membranes. In this study, we evaluated microbial activity in soils of the Atacama Desert, Chile, by analysing several biomarkers, including phosphatase activity. Phosphatases extracted with Tris buffer were assayed fluorometrically using 4-methylumbelliferyl phosphate as a substrate. The horizontal distribution of phosphatase activity and other parameters in soils from the Atacama Desert showed that phosphatase activity was positively correlated with amino acid concentration and colony-forming units and negatively correlated with precipitation amount. We found consistent that biochemical indicators including phosphatase significantly decreased in the extreme hyper-arid zone where rainfall of <25 mm year −1 . The results were compared with phosphatase activities detected in extreme environments, such as submarine hydrothermal systems and Antarctic soils, as well as soils from ordinary environments. Overall, our results suggested that phosphatase activity could be a good indicator for evaluating biological activities in extreme environments.